Setter decision-making in elite volleyball: a systematic review of perceptual, tactical, and contextual factors - Rudyanto Rudyanto; Ikhwanul Arifan; Bram Sujadesman (Indonesian Institute For Counseling, Education and Therapy, 2025)
The setter is the main tactical thinker in volleyball who can turn the team's uncertain reception into an effective attack based the quick perceptual and decision-making process of a setter. However, the research on the decision-making of a setter is still very limited and scattered among performance analysis, ecological dynamics, and sensing technologies. A systematic literature review was conducted to integrate the findings on perceptual-cognitive elements, attack distribution patterns, and contextual constraints that determine the behavior of elite volleyball setters. A search was done in Scopus with the PRISMA 2020 guidelines and a Boolean query, resulting in 466 records. After eliminating duplicates, screening, and assessment of eligibility, only 10 articles were selected for qualitative synthesis and evaluated with the FICO framework (Focus, Information, Context, Outcome). The results showed that the setter's decision-making is most of the time dependent on the spatiotemporal relations between setters, attackers, and blockers. Under normal side-out situations the attack distribution is largely directed to the middle and wing attackers. The quality of the opponent has less influence than the team's offensive strategy, while setting behavior is largely determined by the rule and task constraints. The review demonstrates that setter decision-making is fundamentally constrained by spatiotemporal affordances emerging from setter-attacker-blocker interactions. Findings support an ecological-dynamics interpretation of tactical expertise and highlight opportunities for integrating wearable sensing, social-network analysis, and machine learning approaches into future volleyball performance research.